MACHINE LEARNING CONTENT-BASED FILTERING WOMEN EMPOWERING RECOMMENDATIONS ON YOUTUBE - Yuliana, Yuliana; Mira, Mira; Hari Kristianto, Aloysius (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: YouTube is one of the most popular video streaming platforms, but it has constraints that can cause problems when clients have difficulty finding content according to their wishes. The main objective of this study is to increase user capacity in viewing content specifically in the field of women’s empowerment. By using content-based filtering techniques, the system will analyze user preferences and interests through recommendations for women’s empowerment content. The data source is via the YouTube API and is analyzed using PHP programming content-based filtering techniques. The system’s recommendations provide a list of women’s empowerment content with a user request display. The results of the research evaluation obtained a precision value of 62%, meaning that the recommendations match the topic being searched for, namely women’s empowerment. The recall value of 84% indicates that the system has succeeded in finding relations from the database. The f1-score value of 72% indicates that there is a balance between precision and recall, meaning that a system is needed that is not only accurate but also complete. While the cosine value shows a score of 0.7071 approaching the maximum value (1.0). The recommendation of the content-based filtering method produces quite effective women’s empowerment content. Keywords: content-based filtering, recommendations, women Empowerment, youtube